MAKANAN USAHA JASA BOGA DI LINGKUNGAN KAMPUS UNIVERSITAS NEGERI PADANG - WIJAYA, ALI; Yuliana, Yuliana; Waryono, Waryono (Journal of Home Economics and Tourism, 2015)
The study aims to determine the application of employee personal hygiene food processors catering business which in terms of: (a) public health, (b) personal hygiene and (c) clothing kitchen food processors in Padang State University campus. This study is a descriptive study with quantitative and qualitative approaches. The type of data in this study in terms of primary data include 1) the owner of a catering business 2) employees of food processing and 3) the customers who visit. This study used purposive sampling technique sampling technique with particular consideration.Â Based on the results of the study found several issues related to the application of the personal hygiene of food processing businesses catering services, namely: 1) in general 50% of informants food processors do not pay attention to sleep and recreation in public health, 2) as much 20% -100% of informants food processors do not pay attention to the cleanliness of hands, fingernails and toes, nose, mouth, teeth and feet, 3) 60% -100% of informants do not pay attention to hygiene food processors used clothing ranging from aprons, headgear and footwear. Keywords: personal hygiene, food processors, food service institution